2014
DOI: 10.1097/wnr.0000000000000146
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the insular nitric oxide signaling pathway in the expression of morphine-induced conditioned place preference in rats

Abstract: Nitric oxide (NO) has been recently reported to play an important role in the rewarding effects of addictive drugs. The regional NO signaling in the brain, however, is not completely clear. Here, we studied the effects of insular NO signaling on the expression of morphine-induced conditioned place preference (CPP). Insular microinjection of the NO inhibitors N-nitro L-arginine methyl ester (L-NAME) and 7-nitroindazole reduced the expression of morphine-induced CPP. The NO donor molsidomine, in contrast, revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Gholami et al have shown that the nitric oxide in the nucleus accumbens might mediate the morphine CPP in rats [ 40 ]. These findings are further corroborated by Peng et al who have demonstrated that insular nitric oxide signalling pathway was involved in the expression of morphine CPP [ 41 ]. In our study, reduced mRNA expression of iNOS as well as nitrite in hippocampus was observed which is in agreement with the previous reports.…”
Section: Discussionsupporting
confidence: 74%
“…Gholami et al have shown that the nitric oxide in the nucleus accumbens might mediate the morphine CPP in rats [ 40 ]. These findings are further corroborated by Peng et al who have demonstrated that insular nitric oxide signalling pathway was involved in the expression of morphine CPP [ 41 ]. In our study, reduced mRNA expression of iNOS as well as nitrite in hippocampus was observed which is in agreement with the previous reports.…”
Section: Discussionsupporting
confidence: 74%
“…Inactivation of the aIC is capable of attenuating relapse to methamphetamine taking following the removal of contingency management (i.e., palatable food pellets mutually-exclusive from drug) (Venniro et al, 2017). The presentation of morphine-induced CPP is also abolished by lesions to the pIC (Sun et al, 2018) or the inhibition of nitric oxide in the pIC (Ma et al, 2014).…”
Section: Preclinical Evidence For the Insulamentioning
confidence: 99%
“…In addition, an array of recent studies using animal models and pharmacological or chemical interventions have showed that insula is involved in different aspects of addictive behavior of various addictive drugs ( 15 20 ). For example, morphine-induced conditioned place preference (CPP) in rats were attenuated in studies using administration of muscarinic acetylcholine receptor antagonists and nitric oxide inhibitors into insula ( 21 , 22 ). Previous work has also confirmed that insula is involved in the neurocircuitry underlying all stages of substance use disorder, and clearly suggested that insula is a fundamental brain region in the maintenance and relapse to addictive drugs ( 23 ).…”
Section: Introductionmentioning
confidence: 99%